(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2024)
The number of people participating in state funded ‘community learning’ has diminished over the last decade from a figure of 657,200 in 2013/14 to just 274, 090 in 2022/2023. Although there are many different interpretations of what community learning is, this article’s key concern is for learning being offered ‘in’ and ‘for’ local communities. From next year, at least from a UK government funding perspective, ‘Community Learning’ will be no more in England. From August 2024 the new term of ‘Tailored Learning’ will be adopted instead, despite having scant provenance within adult learning. Such a name change suggests a neo-liberal political ideology and strengthens the current argument that adult learning which is paid for by the state should be for employment purposes, or a steppingstone to employment only. Will the new term act as a marker of increased focus on meeting individual needs, or will learning be increasingly tailored to meet employer needs? It can of course be argued that ‘Tailored Learning’ will seek to achieve both ends but, even if this is the case, the pendulum may well have swung even further towards state-funded adult learning being the facilitator of a relationship between the individual and employers. With an election looming, ‘Tailored Learning’ could either be a short-lived or a long-term change. On the surface, a change of name and re-categorisation of purposes does not mean that adult learning cannot continue to take place ‘in’ and ‘for’ communities. However, it does take adult learning further along the tracks of ‘efficiency’ and ‘utility’ and is therefore worthy of continued critical debate.